PEMILIHAN PEGAWAI BERPRESTASI DI LINGKUNGAN YAYASAN TP 45 NEGARA BERBASIS SISTEM PENUNJANG KEPUTUSAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING - I Nengah Juniawan; Ida Bagus Kade Dwi Suta Negara (Badung: LPPM Universitas Triatma Mulya, 2019)
The quality of human resources is one of the supporting factors to improve the productivity of the performance of an agency or organization. Therefore, competent human resources can support the level of performance, with the performance appraisal will be known that the achievements of each employee, this makes it easy for agencies or organizations to consider in determining the best employees. Decision Support System is a system that is able to manage data and provide the best alternative solutions. The selection of outstanding employees is determined based on criteria and weights, namely: the level of attendance, accuracy of work assignments, leadership, and length of service. Furthermore, the data from the employee is processed using the Simple Additive Weighting (SAW) method. This Simple Additive Weighting (SAW) method gives a weighting to each of the criteria used to produce the best alternative value. With this system, it is expected to be able to assist in faster decision making in high achieving employees within the TP 45 Negara Foundation.